Murābaḥa Reconstruction: Its Application in the Electronic Journal in Indonesia - Muhammad Hasan (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
This study aims to look at changes in murābaḥa, both in terms of theory and practice in contemporary banking. Contemporary murābaḥa practices refer to articles and research results that are circulating very dynamically and in some aspects undergo an update or modification. This research explores contemporary scientific articles on murābaḥa circulating in cyberspace, which do not experience changes at the concept level but a change in practice. Murabaha, like special sales, often does not appear to be a murābaḥa practice, even the terms of the sale and purchase agreement cannot be done. This study found that murābaḥa changed in terms of contracts, pricing, and some conditions.